Classroom-based Assessment Practices for Learning - Gupta, Sweta (JOURNAL OF INDIAN EDUCATION, 2023)
The present paper recognises the importance of Assessment for Learning (AfL) in enhancing students’ learning. Attempts have been made to translate the theory of AfL to actual classroom practices. Such assessment, when used with classroom instructions, provides the scope to improve students’ learning. Herein, feedback, one of the significant components of AfL is used to find the learning gap; thereby, helpful information is provided to students, which scaffolds their present performance to reach the desired level. Many such practices have been elaborated on in this paper to help the teachers better understand AfL. The paper attempts to highlight the potential power of formative assessment which, when used with summative assessment, contributes to improving the students’ learning, raising the quality of education.